2017
DOI: 10.1007/s12013-017-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

Fish Collagen Hydrolysates Modulate Cartilage Metabolism

Abstract: Osteoarthritis is a degenerative joint disease in which interleukin-1β plays a major role in the inflammatory process. Administration of collagen hydrolysate was an optional treatment of osteoarthritis. Fish has become an interesting source of collagen hydrolysate because of religious reason and there is no risk from mad cow disease. However, the effects of different sizes of fish collagen hydrolysate on cartilage and chondrocyte metabolism have not been well studied yet. This study examined the effect of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…This gives rise to the repeat occurrence of AHTPs of GLP and LPG. Furthermore, their bioactivities demonstrate their remarkable advantages in various fields [ 42 , 43 ]. For example, Vastatin, an endogenous antiangiogenic polypeptide from non-collagenous C-terminal globular domain of col8a1, has been reported to be promising in fighting against glioblastoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This gives rise to the repeat occurrence of AHTPs of GLP and LPG. Furthermore, their bioactivities demonstrate their remarkable advantages in various fields [ 42 , 43 ]. For example, Vastatin, an endogenous antiangiogenic polypeptide from non-collagenous C-terminal globular domain of col8a1, has been reported to be promising in fighting against glioblastoma [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These exciting results have, however, been moderated by findings from two in vitro studies conducted by the same research group from Germany, which compared different CH preparations (different sources and sizes) and concluded that CHs from various sources differed in terms of their peptide composition and were either ineffective or even detrimental to OA cartilage [43,44]. Similar findings were reported by a subsequent study from Thailand, published in 2018, which compared fish CH of different molecular weights [41]. Besides the results from these in vitro studies, the findings from the in vivo studies have been confirmed by clinical studies in OA patients.…”
Section: Discussionmentioning
confidence: 76%
“…Types of Studies A total of 41 studies have been published on collagen derivatives in OA and cartilage repair so far. Sixteen of these studies were preclinical in vitro and in vivo studies [25,26,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] and 25 were clinical studies (including clinical trials, observational studies, and systematic reviews/ meta-analyses) [27,28,31,. Figure 2 depicts the distribution of the studies by specific study type.…”
Section: Description Of Evidence On Collagen Derivatives In Oa and Camentioning
confidence: 99%
See 1 more Smart Citation
“…HC is also a therapeutic agent that has been used for long‐term treatment of OA owing to HC's high safety (Oesser et al ., ). At the same time, HC had no effect on cartilage metabolism (Boonmaleerat et al ., ). Guillerminet et al .…”
Section: Introductionmentioning
confidence: 97%